An ontology-based approach to support the certification of Safety-Critical Software Product Lines - Bressan, Lucas; Braga, Regina; Campos, Fernanda; Oliveira, André (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2020)
Safety-critical Product Lines are required to demonstrate compliance with domain-specific safety standards. Different component configurations may require the inclusion or exclusion of certain features depending on their impact on safety. Additionally, variants may present distinct criticality levels which imply in different safety requirements during their development and evaluation. Some authors have proposed approaches to address safety certification taking into account SPL Engineering (SPLE) activities. Those can be however, labor intensive and impracticable when dealing with larger and complex product lines. In this paper, we propose an ontology-based approach to support safety engineers on identifying features and assets relevant for the deployment and certification of safety-critical product lines. The approach was evaluated, considering a realistic SPL from the aerospace domain and the DO-178C safety standard. As a result, the application of the proposed approach was proven to support the traceability of SPL requirements and certification levels, thus, reducing the complexity of the deployment of different component configurations.